Perancangan Manajemen Acara untuk Telkom Corporate University Center (Periode Agustus-Desember 2023) - Ajibroto, Daffa Diovani; Dirgantara, Pradipta (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research designs an event management plan for the Telkom Corporate University Center during August-December 2023. This research explores knowledge transfer strategies through webinars, evaluates their effectiveness, and their impact on audience perception and engagement. The results show the importance of communication in conveying the company's strategic messages and enriching employees' understanding of the competitive business environment. Observation and documentation methods are used to strengthen research design and develop effective event management practices. The conclusion emphasizes the need for employee optimization and knowledge transfer to create human resources that are ready to compete. Despite facing budget and time challenges, the final results of this event demonstrated a positive response from webinar participants and maintained the company's professional image